2017
DOI: 10.1016/j.pharep.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of l-thyroxine treatment on sexual function and depressive symptoms in men with autoimmune hypothyroidism

Abstract: The obtained results suggest that autoimmune hypothyroidism in men is characterized by sexual and mood disturbances and that hypothyroid patients with sexual dysfunction and depressive symptoms benefit from L-thyroxine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…The present findings are in contrast with our previous research, which showed that impaired erection was the only sexual dysfunction observed in men with subclinical hypothyroidism as well as a domain most seriously affected in patients with overt hypothyroidism [9]. Moreover, correlations between erectile functioning and thyrotropin and free thyroid hormone levels were stronger than for the remaining domains of IIEF-15 [9].…”
Section: Prace Oryginalnecontrasting
confidence: 99%
See 2 more Smart Citations
“…The present findings are in contrast with our previous research, which showed that impaired erection was the only sexual dysfunction observed in men with subclinical hypothyroidism as well as a domain most seriously affected in patients with overt hypothyroidism [9]. Moreover, correlations between erectile functioning and thyrotropin and free thyroid hormone levels were stronger than for the remaining domains of IIEF-15 [9].…”
Section: Prace Oryginalnecontrasting
confidence: 99%
“…Moreover, correlations between erectile functioning and thyrotropin and free thyroid hormone levels were stronger than for the remaining domains of IIEF-15 [9]. These differences may reflect the direct impact of chronic levothyroxine treatment (participants of the previous study were levothyroxine-naïve) and/or different inclusion criteria.…”
Section: Prace Oryginalnementioning
confidence: 91%
See 1 more Smart Citation
“…The study purposely included only men with thyrotropin and free thyroid hormone levels within the reference range. Taking into account that patients with autoimmune hypothyroidism should receive thyroid hormone replacement, as well as that exogenous levothyroxine reduces thyroid antibody titres, excluding men with thyroid hypofunction minimized the possibility that the alleviation of thyroid autoimmunity is a consequence of the effect of levothyroxine (not testosterone) or is secondary to pharmacokinetic or pharmacodynamic interactions between levothyroxine and testosterone. Because the study population consisted of only drug‐naïve subjects, the obtained results cannot be also explained by a modulatory impact of testosterone on other medications found to reduce thyroid antibody titres (vitamin D, selenium, myo‐inositol or statins) …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, androgens receptors were found in the thyroid gland, testosterone up‐regulated androgen receptors in rats and induced thyrocyte proliferation . Finally, exogenous levothyroxine reduced titres of TPOAb and TgAb in men with autoimmune thyroiditis . Therefore, it is also possible that increased endogenous thyroxine production induced by testosterone administration behaves similarly to exogenous levothyroxine.…”
Section: Discussionmentioning
confidence: 99%